Bibliometric analysis of emerging technologies in the field of computer science helping in ovarian cancer research - Kothari, Dr. Sonali; Gupta, Anvita; Agrawal, Muskaan; Jaggi, Kajal; Goswami, Adhiraj; Kotecha, Ketan; Dr, Karthikeyan; Khedkar, Vijayhsri (Library Philosophy and Practice, 2021)
This study is carried out to provide an analysis of the literature available at the intersection of ovarian cancer and computing. A comprehensive search was conducted using Scopus database for English-language peer-reviewed articles. The study administers chronological, domain clustering and text analysis of the articles under consideration to provide high-level concept map composed of specific words and the connections between them.